Maternal and Child Sexual Abuse History: An Intergenerational Exploration of Children’s Adjustment and Maternal Trauma-Reflective Functioning - Borelli, Jessica L.; Cohen, Chloe; Pettit, Corey; Normandin, Lina; Target, Mary; Fonagy, Peter; Ensink, Karin (Frontiers in Psychology, 2019)
Objective: The aim of the current study was to investigate associations, unique and interactive, between mothers’ and children’s histories of childhood sexual abuse (CSA) and children’s psychiatric outcomes using an intergenerational perspective. Further, we were particularly interested in examining whether maternal reflective functioning about their own trauma (T-RF) was associated with a lower likelihood of children’s abuse exposure (among children of CSA-exposed mothers). Methods: One hundred and eleven children (Mage = 9.53 years; 43 sexual abuse victims) and their mothers (Mage = 37.99; 63 sexual abuse victims) participated in this study. Mothers completed the Parent Development Interview (PDI), which yielded assessments of RF regarding their own experiences of abuse, and also reported on their children’s internalizing and externalizing symptoms. Results: Children of CSA-exposed mothers were more likely to have experienced CSA. A key result was that among CSA-exposed mothers, higher maternal T-RF regarding their own abuse was associated with lower likelihood of child CSA-exposure. Mothers’ and children’s CSA histories predicted children’s internalizing and externalizing symptoms, such that CSA exposure for mother or child was associated with greater symptomatology in children. Conclusion: The findings show that the presence of either maternal or child CSA is associated with more child psychological difficulties. Importantly in terms of identifying potential protective factors, maternal T-RF is associated with lower likelihood of CSA exposure in children of CSA-exposed mothers. We discuss these findings in the context of the need for treatments focusing on increasing T-RF in mothers and children in the context of abuse to facilitate adaptation and reduce the intergenerational risk.